Industry 4.0: technical qualifications for the fourth industrial revolution in Brazil - Villalba, Felipe Zenin; Peinado, Jurandir; Vianna, Fernando; Meneghetti, Francis (Revista Gestão da Produção Operações e Sistemas, 2022)
Purpose – To research and present the manner in which the technical qualifications needed for Industry 4.0 (I4.0) are addressed by graduate courses studied and manufacturing companies in Brazil. Theoretical framework – New technical requirements linked to the new I4.0 scenario imply the need to provide new forms of training for the workforce. This requirement has become important both for workers to remain competitive in the job market, as well as for the organizations themselves within the business market. Design/methodology/approach – A document review of the syllabuses and subjects of 24 lato sensu graduate courses studied and 56 job vacancies related to I4.0, which classifies this study as a time-restricted and exploratory study. Findings – The results show that, of the nine technological categories of I4.0 researched, greater importance is placed on Big Data (58%) and integrated systems (36%) by companies, and in graduate courses studied, importance is placed on Big Data (29%), the Internet of Things (14%), integrated systems (13%) and information security (12%). Research, practical and social implications – The main practical and social implications of this study are related to a need for HEIs to discuss a common set of knowledge with businesses regarding various areas of training. Originality/value – This study contributes to the identification of the skills needed by workers in I4.0 to warn company HR departments regarding the need for training in these skills, and the need in turn for companies to be aware of the complexity that I4.0 represents. Keywords - Industry 4.0; Technology I4.0; Jobs; Education.